Do We Have to Perform a Renal Biopsy? Clinical Dilemmas in a Case with Nephrotic Syndrome. Issue 7 (January 2014) - Akimoto, Tetsu; Otani, Naoko; Takeshima, Eri; Saito, Osamu; Kusano, Eiji; Nagata, Daisuke
Renal biopsy is one of the pivotal diagnostic tools used in the field of nephrology. A morphological analysis of the kidney may also be of value for the overall management of patients with diabetic nephropathy. However, the indications for renal biopsy differ considerably among nephrologists, and no global consensus regarding performing this procedure among diabetic patients with various renal manifestations has yet been achieved. In this report, we would like to describe our serendipitous experience with a male type 2 diabetic patient presenting with nephrotic syndrome complicated by concurrent gastric carcinoma. We also discuss several conundrums that arose in the current case, which had an impact on our diagnostic and therapeutic decisions.